2009
DOI: 10.5194/angeo-27-1605-2009
|View full text |Cite
|
Sign up to set email alerts
|

Storm induced large scale TIDs observed in GPS derived TEC

Abstract: Abstract. This work is a first statistical analysis of large scale traveling ionospheric disturbances (LSTID) in Europe using total electron content (TEC) data derived from GNSS measurements. The GNSS receiver network in Europe is dense enough to map the ionospheric perturbation TEC with high horizontal resolution. The derived perturbation TEC maps are analysed studying the effect of space weather events on the ionosphere over Europe.Equatorward propagating storm induced wave packets have been identified durin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

7
105
1

Year Published

2010
2010
2015
2015

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 80 publications
(118 citation statements)
references
References 19 publications
(21 reference statements)
7
105
1
Order By: Relevance
“…They are frequently observed through GPS measurements or by ionosondes in middle-and high-latitude regions such as North America (Nicolls et al, 2004;Ding et al, 2007Ding et al, , 2008 and Europe (Borries et al, 2009). They are also commonly observed in middle-and low-latitude regions such as Japan , Brazil (Klausner et al, 2009;de Abreu et al, 2010), and China .…”
Section: Discussionmentioning
confidence: 99%
“…They are frequently observed through GPS measurements or by ionosondes in middle-and high-latitude regions such as North America (Nicolls et al, 2004;Ding et al, 2007Ding et al, , 2008 and Europe (Borries et al, 2009). They are also commonly observed in middle-and low-latitude regions such as Japan , Brazil (Klausner et al, 2009;de Abreu et al, 2010), and China .…”
Section: Discussionmentioning
confidence: 99%
“…Our results can be compared with storm-induced large-scale travelling ionospheric disturbances (LSTID). Borries et al (2009) reported recently about LSTID observations over Europe. Their waves are also excited in the auroral region and propagate equatorward at a similar speed (680 m/s on average).…”
Section: Thermospheric Mass Density Effectsmentioning
confidence: 99%
“…The ionization front and related perturbation pattern can be detected and traced by more adequate techniques such as wavelet analysis (cf. Borries et al 2009). Here the propagation is mostly southward.…”
Section: à2mentioning
confidence: 99%
“…Later we see a number of perturbation traces propagating towards Southern Europe. The slopes indicate velocities in the order of 600 m/s typically for large-scale perturbation pattern (e.g., Borries et al 2009). In the afternoon around 15:00 UT starts the equatorward motion of the high-latitude trough which separates polar patches in the north from more regular transport processes in the south.…”
Section: à2mentioning
confidence: 99%
See 1 more Smart Citation